Kalibrasi Arah Kiblat Masjid Al Jumu’ah Pondok Pesantren Karomatul Qur’an Tanjungpinang - Angkat, M. Arbisora; Hidayatullah, Rizki Pradana; Sari, Afna Fitria; Saniah, Mahfuzah (MENARA RIAU, 2022)
Currently determination the qibla direction is very easy to do, like using the compass from smartphone, but the results shown isn’t always accurate. Compass from one smartphone to another can show different numbers because of the area and surrounding objects, such as iron and magnetic deviation. Many mosques deviate from their qibla direction after calibrating the qibla direction. This happened because at the beginning of measuring the qibla direction of the mosque using the compass, like was happened to Al Jumu'ah Mosque. The purpose of community dedication is to correct the qibla direction of Al Jumu'ah Mosque in order to strengthen the belief in the worship of Karomatul Qur'an Islamic Boarding School Tanjungpinang’s residents. The method uses a consultative approach where community problems and needs are handled in collaboration with universities. After calibrating the qibla direction using the Theodolite, it’s obtained that the azimuth kiblat of Al Jumu'ah Mosque is 293o 06’ 19.49”, be discovered deviation amount 00o 05’ 00”.